PERFORMA REKRUT KARANG HERMATIFIK PADA METODE FISH HOME DI TELUK PALU - Akbar, Mohamad; Wahyudi, Deddy (KAUDERNI : Journal of Fisheries, Marine and Aquatic Science, 2016)
This study examines the coral reefs hermatifik Recruited naturally in concrete substrates (fish home), physical and chemical parameters of waters. Assessment the performance of the reef include health (survival), the growth of coral, coral functional groups as well as the identification of the types of reef fish recruited to the fish home. The research was conducted in the waters of the Palu bay, Mamboro Village North Palu district and Lero village, Sindue district Donggala, Central Sulawesi Province. The research was conducted July to September 2016. Data collection techniques using the method of the survey with random systematic data collection. Position and depth of fish home homogeneous. Visual observation of the census by direct observation using SCUBA at fish home that has been installed in the Water of Lero and Mamboro village. The research results showed the water conditions in the Lero and Mamboro is still good for the growth of coral recruitment. Composition recruit fish on the fish home consists of three groups of fish targets, indicator fish and other fish (major). The index value of diversity recruitment of fish (H ') in the waters of Lero and Mamboro is in the medium category, the index value fish recruits uniformity (E) is not uniform, and the dominance of index valuesrecruit fish (C) in a stable condition.